Pandemic prospects and the global economic recovery - Steven B. Kamin; John Kearns (American Enterprise Institute (AEI), 2021)
This paper develops an empirical model of the economic impact of COVID-19 and uses it to gauge how the evolution of the pandemic will affect the global economic recovery.
Keywords: A; 330; Coronavirus; Developing Countries; Economic Recovery; Global Economy